2010
DOI: 10.1149/1.3502605
|View full text |Cite
|
Sign up to set email alerts
|

High Performance MOCVD-Grown ZnO Thin-Film Transistor with a Thin MgZnO Layer at Channel/Gate Insulator Interface

Abstract: ZnO thin-film transistors (TFTs) with and without a thin MgZnO layer at the channel/gate insulator interface were fabricated using glass substrates. Both ZnO and MgZnO films were grown by metal organic chemical vapor deposition (MOCVD). The ZnO TFTs employing the MgZnO layer exhibit high performance with a field-effect mobility (μFE) of 9.1cm2∕Vs , a subthreshold slope (S) of 0.38V∕dec , an on/off current ratio of 2.3×108 , and a turn-on voltage of −2.75V . This is the best performance reported to date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…The discovery of MgxZn1-xO based materials enables one to fabricate ZnO based nano layers and superlattices which are crucial in the fabrication of ZnO based optoelectronic devices (Gruber et al 2004). To this day, there are a vast numbers of deposition techniques that have been utilized in the preparation of ZnO and MgZnO thin films, among them are radio frequency magnetron (RF) sputtering, pulse laser deposition (PLD) technique, chemical vapour deposition (CVD), and molecular beam epitaxy (Stringfellow, 1999: Remashan et. al., 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of MgxZn1-xO based materials enables one to fabricate ZnO based nano layers and superlattices which are crucial in the fabrication of ZnO based optoelectronic devices (Gruber et al 2004). To this day, there are a vast numbers of deposition techniques that have been utilized in the preparation of ZnO and MgZnO thin films, among them are radio frequency magnetron (RF) sputtering, pulse laser deposition (PLD) technique, chemical vapour deposition (CVD), and molecular beam epitaxy (Stringfellow, 1999: Remashan et. al., 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the fact that the ionic radius of Mg 2+ (0.57Å) is very close to that of Zn 2+ (0.6Å), the Mg Zn 1− O alloy with Mg content = 0.36 remains a single phase wurtzite structure [4]. Recently, several researches reported that Mg Zn 1− O films were prepared by various techniques, such as molecular beam epitaxy (MBE) [5,6], metal organic chemical vapor deposition (MOCVD) [7,8], magnetron radio frequency (RF) sputtering [9,10], vapor cooling condensation system [11], and pulsed laser deposition (PLD) [12,13]. In this work, the high quality Mg 0.1 Zn 0.9 O films were deposited using an atomic layer deposition (ALD) and applied in the metal-semiconductor-metal ultraviolet photodetectors (MSM-UPDs).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the composition of the films can be altered easily by adjusting different ion proportions in the solution [16]. MgZnO films have been developed by other researchers for several device applications such as thin film transistor, resonator, metal-semiconductormetal (MSM) solar blind photo-detector and ultraviolet light emitting diode (LED) [17][18][19][20]. The films were also reported to be compatible as a seed layer for carbon nanotubes [21,22].…”
Section: Introductionmentioning
confidence: 99%